1995
DOI: 10.3382/ps.0741884
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Potassium Sorbate and Lactic Acid on the Shelf-Life of Vacuum-Packed Chicken Meats

Abstract: In this research, the effects of 5% potassium sorbate (PS) and 3% lactic acid (LA) applications on total mesophylic aerobic bacteria, total psychrotrophic aerobic bacteria, lactic acid bacteria, staphylococci and coliform bacteria, pH values, thiobarbituric acid (TBA) numbers, and sensorial properties of vacuum-packed chicken leg and breast meats were investigated during storage at 4 +/- 1 C. In addition, residual sorbate was examined. A decrease in bacterial counts of chicken leg and breast meats was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
5
14
0
Order By: Relevance
“…enteritidis, compared to other Salmonella species, has been reported to be more resistant to lactic acid (Kolsarici & Candogan, 1995;Gill & Badoni, 2004). Özdemir et al (2006) reported 0.05 and 0.70 log reductions of S. typhymurium counts in beef treated with 1% and 2% lactic acid, respectively.…”
Section: Evects Of Lactic Acid On L Monocytogenes S Enteritidis Anmentioning
confidence: 96%
“…enteritidis, compared to other Salmonella species, has been reported to be more resistant to lactic acid (Kolsarici & Candogan, 1995;Gill & Badoni, 2004). Özdemir et al (2006) reported 0.05 and 0.70 log reductions of S. typhymurium counts in beef treated with 1% and 2% lactic acid, respectively.…”
Section: Evects Of Lactic Acid On L Monocytogenes S Enteritidis Anmentioning
confidence: 96%
“…Similar results were obtained by Ismail et al (2001), who reported that immersion of chicken wings in 2% lactic acid caused a significant reduction in numbers of aerobic bacteria. Also, Kolsarici and Candogan (1995) observed that number of total psychrotrophic aerobic bacteria, staphylococci and coliform bacteria on chicken leg and breast meats was decreased after treatment with lactic acid and storage at 4 ± 1 ºC. Also, lactic acid (0.2% and 0.1%) lowers the pH of the medium to 3.61 and 4.03, respectively; and C. freundii is not able to grow at this pH.…”
Section: Discussionmentioning
confidence: 91%
“…5 and 6). Kolsarici and Candogan (1995) reported that potassium sorbate treatment resulted in decreases in bacterial counts and high TBA values in vacuum-packed chicken leg and breast meats during storage at 3-5°C. Negbenebor, Balami, and Igene (1995) made beef patties with pre-rigor beef strips which had been treated with 4% potassium sorbate.…”
Section: Resultsmentioning
confidence: 98%